(untitled) (PANGEEA, 2025)
Recent climate studies have signaled alarming fluctuations in the optimal functioning of the global ecosystem as a result of human intervention. Such changes are visible in the form of increased averages of annual temperatures by several degrees as well as in the the emergence of extreme weather events and hydrological hazards